Longitudinal in vivo biodistribution of nano and micro sized hydroxyapatite particles implanted in a bone defect - Liu, Yang; Sebastian, Sujeesh; Huang, Jintian; Corbascio, Tova; Engellau, Jacob; Lidgren, Lars; Tägil, Magnus; Raina, Deepak Bushan (Frontiers in Bioengineering and Biotechnology, 2022)
Hydroxyapatite (HA) has been widely used as a bone substitute and more recently as a carrier for local delivery of bone targeted drugs. Majority of the approved HA based biomaterials and drug carriers comprise of micrometer sized particulate HA (mHA) or granules and can therefore only be used for extracellular drug release. This shortcoming could be overcome with the use of cell penetrating HA nanoparticles (nHA) but a major concern with the clinical use of nHA is the lack of data on its in-vivo biodistribution after implantation. In this study, we aimed to study the in-vivo biodistribution of locally implanted nHA in a clinically relevant tibial void in rats and compare it with mHA or a combination of mHA and nHA. To enable in-vivo tracking, HA particles were first labelled with 14C-zoledronic acid (14C-ZA), known to have a high binding affinity to HA. The labelled particles were then implanted in the animals and the radioactivity in the proximal tibia and vital organs was detected at various time points (Day 1, 7 and 28) post-implantation using scintillation counting. The local distribution of the particles in the bone was studied with micro-CT. We found that majority (>99.9%) of the implanted HA particles, irrespective of the size, stayed locally at the implantation site even after 28 days and the findings were confirmed using micro-CT. Less than 0.1% radioactivity was observed in the kidney and the spleen at later time points of day 7 and 28. No pathological changes in any of the vital organs could be observed histologically. This is the first longitudinal in-vivo HA biodistribution study showing that the local implantation of nHA particles in bone is safe and that nHA could potentially be used for localized drug delivery.